The characterization of CellROX™ probes could be a crucial factor in ram sperm quality assessment - Palacin-Martinez, Cristina; Anel-Lopez, Luis; Alvarez, Mercedes; Neila-Montero, Marta; Montes-Garrido, Rafael; Soriano-Úbeda, Cristina; de Paz, Paulino; Anel, Luis; Riesco, Marta F. (Frontiers in Veterinary Science, 2024)
Several authors have demonstrated that low levels of reactive oxygen species (ROS) are necessary for the physiological functions of sperm, such as capacitation, hyperactivation, acrosomal reaction and fertilization. However, high levels of ROS are associated with oxidative stress and detrimental effects on fertility. Consequently, deep characterization of ROS presence using different fluorescent probes could be crucial. In this sense, the study of intracellular ROS localization and the relationships between ROS and other conventional parameters could improve the characterization of sperm quality for semen preservation protocols in rams. In this work, a multiparametric study was carried out by analyzing four experimental groups of ram sperm with different initial qualities: fresh semen (from both breeding and nonbreeding seasons), frozen-thawed semen and, a positive control group treated with hydrogen peroxide (300 μM) as a marker of extreme damage. Sperm analyses, including viability, apoptosis, lipid peroxidation, motility and kinetic parameters, were applied to compare several experimental groups with different sperm qualities. After that, the signals from two different ROS probes: CellROX™ Deep Red (CRDR) and Green (CRG), were examined by flow cytometry (percentage of cells that express ROS) and fluorescence microscopy (intracellular ROS location). Comparing conventional parameters, fresh samples from the breeding season showed the highest sperm quality, while the positive control samples showed the worst sperm quality. Concerning the ROS probes, the CRDR levels were higher in fresh samples from the breeding season than in the positive control and cryopreserved samples. Surprisingly, CRG presented its highest level (P < 0.05) in the positive control group treated with peroxide by flow cytometry. CRDR and CRG presented opposite labeling patterns that were corroborated by fluorescence microscopy, which determined that the probes localized in different parts of sperm. CRDR was found in the sperm mitochondrial region, while CRG was observed in the cell nucleus, suggesting that ROS localization is an important factor. Finally, our study indicates that CRDR is correlated with viability and sperm motility, and could be associated with high mitochondrial activity, while CRG is associated with sperm damage.